2018
DOI: 10.1093/eurpub/cky078
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effect of the financial crisis in Greece on perinatal factors

Abstract: The financial crisis has possibly adversely affected perinatal factors in Greece. Our results highlight the need of appropriate public health interventions and family support policies, especially for younger people, unemployed and immigrants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…16 Preterm birth and LBW increased by 37% and 7% respectively in Greece the years 2011-14. 27 In Iceland, small for gestational age increased from 2% to 3.4%. 26 Absolute inequalities in infant mortality rates (IMR) in England increased in 1990-1999 (annual changes between the most deprived local authorities and the rest of England: 0.03), decreased during the welfare strategy period 2000-2010 (-0.11) and increased in 2011-2017 (0.04) after the end of this strategy.…”
Section: Child Health Outcomes (Cho)mentioning
confidence: 99%
“…16 Preterm birth and LBW increased by 37% and 7% respectively in Greece the years 2011-14. 27 In Iceland, small for gestational age increased from 2% to 3.4%. 26 Absolute inequalities in infant mortality rates (IMR) in England increased in 1990-1999 (annual changes between the most deprived local authorities and the rest of England: 0.03), decreased during the welfare strategy period 2000-2010 (-0.11) and increased in 2011-2017 (0.04) after the end of this strategy.…”
Section: Child Health Outcomes (Cho)mentioning
confidence: 99%
“…Rajmil 2018 et al 16 LBW increased during the period 2012-15 in those countries with higher austerity (interaction austerity*period 2012-15, B: 0.25; p = 0.004) Zografaki et al 2018 27 LBW Health care professionals reported worsening quality of services than 3 years ago: increased waiting times, and less time allocated to see each child compared to 3 years ago, and worse working conditions in the last year. Nine in every ten families reported worsening quality of services for their disabled children compared to 3 years ago.…”
Section: First Author Main Resultsmentioning
confidence: 99%
“…16 Preterm birth and LBW increased by 37% and 7% respectively in Greece the years 2011-14. 27 In Iceland, small for gestational age increased from 2-3.4%. 26 10 Table 3 Child health and healthcare services…”
Section: Percentage Of Children Living In Poverty Almost Not Modifiedmentioning
confidence: 98%
“…Child health and healthcare servicesRajmil 2018 et al16 LBW increased during the period 2012-15 in those countries with higher austerity (interaction austerity*period 2012-15, B: 0.25; p=0.004) Zografaki et al201827 LBW increased (Standardised rate ratio, SRR= 1.07[1.06-1.09]), as well as preterm births (SRR=1. [1.37-1.42] during established crisis.…”
mentioning
confidence: 99%